Analisis Kinerja Pelayanan Air Bersih PDAM Tirta Daroy Kota Banda Aceh - Haiqal Haiqal; Azmeri Azmeri; Eldina Fatimah (Prodi Magister Teknik Sipil Unsyiah, 2020)
Perusahaan Daerah Air Minum (PDAM) is a business entitiy owned by the Aceh government which has business scope in managing drinking water and managing fresh water facilities to improve the welfare of the city citizens.. PDAM Tirta Daroy is an agency that serves the drinking and fresh water distribution for Banda Aceh city, in the 2017 PDAM Tirta Daroy has achieved “Health” status woth value 3,11 which is ranked 130 out of 378 PDAM assessed throughout Indonesia. Even though PDAM Tirta Daroy has achieved health status there are still customers who complaint receiving distribution of fresh water with very disssapointing quality so that the analyses study of fresh water is needed for the PDAM Tirta Daroy in 2018. The problem in this study is how the performance of PDAM Tirta Daroy fresh water services in 2018. The purpose of this study is to determine the performance of PDAM Tirta Daroy against the fresh water supply system in Banda aceh city and PDAM Tirta Daroy strategy in improving performance related to the current fresh water services. The research methodology initially began with the collecting the primary and secondary data, the interviews results are written descriptively in accordance with the activities that occur. After conducting primary and secondary data in 2018 data then processed using Balance Scorecard and SWOT analysis. The results of this study is to find out the value of PDAM performance based on the 4 aspects of Balanced Scorecard which are financial aspects, services, operational, and Human resources aspects, and the PDAM Tirta Daroy strategy in an effort to improve the problems of fresh water services in Banda Aceh city.